Retrospective Study On Cystic Echinococcosis in Livestock in Northern Türkiye - Dal, Ayşe Gül; Terzi̇, Funda; Dal, Fatmanur; Pehli̇van, Şakir; Türlek, Şakir Önder; Kaya, Selma; Çibik, Recep; Dal, Ayşe Gül; Terzi̇, Funda; Dal, Fatmanur; Pehli̇van, Şakir; Türlek, Şakir Önder; et al. (Universidad de Cordoba, 2023)
Objective. This study was conducted retrospectively to assess the cystic echinococcosis status of farm animals from the samples sent to Samsun Veterinary Control Institute of the Republic of Türkiye, Ministry of Agriculture and Forestry, between January 2016 and December 2022. Materials and Methods. A total of 818 sheep, 160 goats, and 990 cattle necropsy materials were examined macroscopically and histopathologically according to World Organisation for Animal Health (WOAH) guidelines. Cysts were detected in 61 of examined materials. Results. The rate of total cystic echinococcosis positivity in farm animals was found to be 3.1% in northern Türkiye. Cysts were detected in at least one of the liver and lungs. It was detected in the liver in 24 cases (39.3%), the lung in 23 cases (37.7%), and both the lung and liver in 11 cases (18%). In addition, cysts were found in both of lung and spleen (1 case), kidney and liver (1 case), and heart and liver (1 case). The positivity rate was higher in sheep than in other ruminants, and the difference with other ruminant species was statistically significant. (p<0.001). The difference between prevalence rates by years was found to be statistically significant (p=0.001). Conclusions. Türkiye is defined as a highly endemic region for Echinococcus granulosus and Echinococcus multilocularis. Surveillance should be done regularly to implement control programs. The information presented in this study will contribute to gaining an idea about the status of cystic echinococcosis in livestock in northern Türkiye and to the development of prevention and control strategies.
Keywords: Equinococosis cística; animales de granja; Sheep; Epidemiology; Granulosus; Hydatidosis; Molecular Characterization; Ruminants; Multilocularis; Cystic echinococcosis; Diagnosis; Prevalence; histopathology; Cattle; prevention and control; postmortem examination; farm animals; histopatología; examen post mortem; prevención y control; 2. Zero hunger; 3. Good health